1971
DOI: 10.1002/jso.2930030408
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the tongue in young persons

Abstract: Carcinoma of the tongue in young persons is uncommon. A search of records of the Memorial Hospital revealed six such cases, and 13 others were encountered in the literature. The preponderance of females in this small series is not significant. The high survival rate (50%) is directly attributed to the infrequency of cervical metastasis and the favorable location (anterior two-thirds) of the primary lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
2
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
2
11
2
1
Order By: Relevance
“…The male–female ratio in the total cases treated during the same period was 1.39:1. Some previous studies have suggested that there is a predominance of females in the younger age groups (7, 24), but most have reported a similar higher number of males (2, 3, 15, 16, 25, 26). Analysis by site showed that 54.3% of cancers arose on the tongue in young patients, compared with 30.9% in older patients, supporting previous studies suggesting that tongue may be more commonly affected in younger patients (reviewed in 15).…”
Section: Discussionmentioning
confidence: 95%
“…The male–female ratio in the total cases treated during the same period was 1.39:1. Some previous studies have suggested that there is a predominance of females in the younger age groups (7, 24), but most have reported a similar higher number of males (2, 3, 15, 16, 25, 26). Analysis by site showed that 54.3% of cancers arose on the tongue in young patients, compared with 30.9% in older patients, supporting previous studies suggesting that tongue may be more commonly affected in younger patients (reviewed in 15).…”
Section: Discussionmentioning
confidence: 95%
“…Eleven studies reported on 94 patients with SCC of the anterior tongue whose TNM stage, treatment, and disease-related outcome at 2 years minimum were known. [4][5][6][7][8][9][10][11][12][13][14] Table 1 provides an overview of the patients and the studies cited.…”
Section: Methodsmentioning
confidence: 99%
“…Prognosis varies from excellent to poor, reflecting the biases and difficulties in reporting small retrospective studies (Table 1). 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In a summary of 14 studies published in the English-speaking literature between 1968 and 1993 involving oral tongue SCC in patients aged less than 40 years old, 152 patients were identified. 26 In 11 of these 14 studies, information regarding loco-regional failure was available, revealing that 57% failed above the clavicles and that 71 (47%) died from their disease.…”
Section: Discussionmentioning
confidence: 99%